Determinan Kepatuhan Membayar Pajak oleh Wajib Pajak Usaha Mikro Kecil Dan Menengah - Ratna Nugraheni (Politeknik Ganesha Medan, 2025)
This research aims to examine the influence of taxpayer awareness, knowledge and understanding, tax sanctions and service quality by the tax authorities on compliance in paying taxes by taxpayers of micro, small and medium enterprises. The sampling technique used in this research is non-probability sampling technique with a purposive sampling method. Determination of the sample size was determined using the Slovin formula. The consideration for using purposive sampling is because the sample in this study was a minimum of 129 micro, small and medium enterprise taxpayers. Data collection in this research was carried out using the technique of distributing questionnaires to be filled in by respondents. Respondents will answer questionnaire questions using a Likert scale. Data were processed using multiple linear regression analysis. The Adjusted R2 value of the multiple linear regression model is 76.3%. This means that the independent variable is able to explain 76.3% of the variability in the dependent variable, while the remaining 23.7% is explained by other variables not included in this research. From the results of the hypothesis test, it is known that taxpayer awareness of micro, small and medium enterprises, tax knowledge and understanding of taxpayers of micro, small and medium enterprises, tax sanctions and the quality of tax services have a significant effect on compliance with paying taxes.